Prevention Harmful Consumption of Alcohol and Drugs in Sao Tome and Principe Through Public Health Communication: The Scientific Protocol - De Santiago, Isabel (2020)
Introduction: Sao Tome and Principe is an African low-and-middle-income country, where extreme poverty causes major health inequalities. No systematic research has been done on the consumption of alcohol and drugs in Sao Tome and Principe, and only overall statistics are available based on the importation of alcoholic drinks and their distribution among the population. There are also no studies on consumption of alcohol and illicit substances in children and youth and no preventive measures being undertaken. Besides that, manual databases present significant limitations, considering the lack of causes associated with mortality rates (0 - 5 years and > 5), and the difficulty to establish a cause/effect relation between diseases, deaths and life expectancy. No relevant data with burden of life was found in the reports of Centro Nacional de Endemias or the non-governmental, organization Instituto Marques de Valle Flor, a facilitator on healthcare clinical specialties selected on a voluntary basis by doctors from Portuguese hospitals. So, we proposed to provide a first overview of family and housing conditions, and above all, the consumption of alcohol and illegal drugs in young people. Thus, a project, the National Survey on Harmful Consumption of Alcohol and Drugs in Schools of Sao Tome and Principe, will be realized in order to better characterize the situation among children and young students and test public health communication strategies and preventive interventions aimed at this target-population. Interventions were designed taking into consideration local sociocultural realities of target audiences. We considered dialect language, single-parent families (matriarchal structure) and polygamy (mostly) in men and a country and governments led by men (patriarchal structure) and, in which the woman’s role, as Food and Agriculture Organization of the United Nations reports, remains overlooked. Subsequently, we will collect traditional alcohols samples from the two main islands for analysis (at Laboratório de Estudos Farmacêuticos and Laboratório Nacional de Engenharia Civil - Portugal) and to determine heavy metals in the production process and impact on burden of life.Material and Methods: In order to characterise the country’s situation in terms of alcohol and illicit substances consumption a literature review was carried out through a search in several international electronic databases, such as those of the World Health Organization, World Health Organization Africa, United Nation, The Lancet and Lancet Global Health, etc. Available data of the following institutions of Sao Tome and Príncipe was also analyzed: National Institute of Statistics, Ministry of Education, Culture and Training and Ministry of Health and Social Affairs. Several interviews with community and church leaders as well as with members of catholic missions were carried out to better understand the local situation. Following this, a nationwide cross-sectional survey of a sample of 2064 students will be carried out. This will include a questionnaire on socio-demographic characteristics, lifestyles, health behaviors/attitudes, alcohol and illicit substances consumption. Finally, based on the overall diagnosis obtained, some edutainment health communication preventive interventions will be tested in the primary schools of three districts (EDUCA_TURTLE) and on the radio journalists (EDUCA_PRESS). These were evaluated by primary school teachers and by radio journalists.